Karakter MEMBANGUN KARAKTER ANAK YANG BERTANGGUNGJAWAB MELALUI CERITA ARANYAKANDA - Gusti Ayu Putu Agung Mirah Febriyanti (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
The purpose of this article is to facilitate us to teach responsible attitude to children, by means of the stories that be found in the books Itihasa and Puraana. Today many children are found not enaugh even no sense of responsibility, not only on the assignment it has but sometimes even in it self they are have not responsibility. Lack of responsible sense can affect a child's morale.Moral shift can be regarded as one indicator of weak understanding of religious values. By means of Aranyakanda not only can make a sense of responsibility in children but indirectly we can also teach the religious values.In the teachings of Hinduism the form of human responsibility is described in the concept of Tri Hita Karana such as of Prahyangan, Palemahan and Pawongan.